018 Physical Activity and Female Sexual Dysfunction: A Lot Helps, but Not Too Much. (1st May 2022) - Maseroli, E.; Rastrelli, G.; Stasi, V. Di; Cipriani, S.; Scavello, I.; Tommaso, T.; Gironi, V.; Castellini, G.; Ricca, V.; Sorbi, F.; Fambrini, M.; Petraglia, F.; et al.
ABSTRACT: Introduction: Research on the relationship between physical activity (PA) and female sexual dysfunction (FSD) is lacking. Objective: To investigate the clinical, psychological, and sexual correlates of PA in women with FSD. Methods: A non-selected series of n=322 pre- and post-menopausal patients consulting for FSD was retrospectively studied. Regular involvement in PA and its frequency (<1 hour/week: sedentary, 1-3 hours/week: active, 4-6 hours/week: very active, >6 hours/week: extremely active) were investigated with a specific question. FSDs, including HSDD (Hypoactive sexual desire disorder) and FGAD (Female genital arousal disorder), were diagnosed according to a structured and clinical interview. Participants underwent a physical examination and a clitoral Doppler ultrasound, and were asked to complete the Female Sexual Function Index (FSFI), Female Sexual Distress Scale-Revised (FSDS-R), Body Uneasiness Test (BUT), and Middlesex Hospital Questionnaire (MHQ). Results: Mean age was 45.1±12.9, mean body mass index was 25.24±6.34 kg/m 2 and 46.3% (n=149) of women were post-menopausal. At multivariate analysis, women engaging in PA (67.4%, n = 217) scored significantly higher in several FSFI domains - including desire, arousal and lubrication (see Table 1) - and showed lower sexual distress and lower resistance of clitoral arteries, as compared to sedentary women. A significant, inverse association between PA and HSDD was observed (see Table 1). In the same adjusted model, the association between PA and the vascular resistance of clitoral arteries, expressed by clitoral PI, retained statistical significance. Mediation analysis demonstrated that the negative association between PA and HSDD was partly mediated by body image concerns (BUT Global severity index), psychopathological symptoms (MHQ total score) and sexual distress (FSDS-R score). These latter two factors also partly mediated the association between PA and a reduced risk of FGAD, whilst a lower BMI was a full mediator in the relationship between PA and FGAD. Finally, extreme PA was associated with significantly worse scores in several psychosexual parameters (i, e, sexual satisfaction – see Figure 1) and histrionic/hysterical symptoms), even compared to a sedentary lifestyle. Conclusions: In women with FSD, PA was associated with better sexual function and clitoral vascularization, lower sexual distress and reduced odds of HSDD and FGAD; the benefits of PA on sexuality were mediated by both psychological and organic determinants; excessive PA was related with a poor overall sexual function and with a low sexual satisfaction. Women consulting for FSD may gain benefits from regular PA; however, physicians should remain alert to the downsides of excessive exercise. Disclosure: Work supported by industry: no.